دور رقابة لجان صفقات الجماعات الإقليمية على مشروعية الصفقة العمومية - زياد, Ziad (Université de M'sila, 2020)
ملخص : تتحلى لجان صفقات الجماعات الإقليمية بمهمة الرقابة لمطابقة الأحكام التشريعية والتنظيمية، وتتوج بمنح التأشيرة إذا اتسمت بالمشروعية، أو برفضها في حالة مخالفة الأحكام التشريعية أو التنظيمية، ويخول لمن يحوز صلاحية اعتماد الصفقة العمومية (الوالي على مستوى الولاية، ورئيس المجلس الشعبي البلدي على مستوى البلدية)، إصدار مقرر التجاوز إذا تعلق الأمر بالمخالفات التنظيمية دون التشريعية، وهذا ما يؤثر على فعاليتها لاسيما أن لجان الصفقات الولائية أو البلدية لا تملك صلاحية إصدار قرارات تنفيذية لمشروعية الصفقة العمومية. Abstract: The regional commissions transaction commitees exercise the oversight function to comply with legislative and regulatory provisions, it culminates in granting the visa if it is legitimate, or in case of violation of legislative or regulatory provisions, it is authorized for those who have the power to approve the transaction ( viceroy at the state level, chairman of the municipal people’s assembly at the municipality level), issuance of the decision to override if it concerns regulatory irregularities without legislation, this affects their effectiveness especially that the state or municipal procurement committees do not have the power to issue executive decisions within the framework of the ligitimacy of the transaction.
Keywords: رقابة ; لجان الصفقات ; الجماعات الإقليمية ; المشرعية